Meningkatkan Kemampuan Membaca Anak Disleksia melalui Pembelajaran Multisensori di Sekolah Dasar - Fikriana, Fikriana; Sarwendah, Titin; Prasasti, Adya Rosa (Peneliti.net, 2026)
Dyslexia is a specific learning disability that originates from neurological factors and significantly impacts a person's reading ability. This study aims to describe the application of multisensory methods to improve the reading ability of students with dyslexia. The study used a qualitative approach with a descriptive design. This article was written to explain the effectiveness of multisensory methods in helping improve the reading ability of students with dyslexia in elementary school. Students with dyslexia require learning strategies that can activate all senses in the process of recognizing and understanding learning materials, making the multisensory method a relevant approach. Through this method, students learn by involving visual, auditory, kinesthetic, and tactile memory in an integrated manner. The results of the study indicate that the multisensory method has been proven to improve the reading ability of students with dyslexia characteristics in elementary school and can be used as an alternative treatment to overcome learning barriers experienced by dyslexic students.